Eurolegalism : the transformation of law and regulation in the European Union - Kelemen, R. Daniel (Harvard University Press, 2011)
Despite western Europe's traditional disdain for the United States' "adversarial legalism," the European Union is shifting toward a similar approach to the law, according to Daniel Kelemen. Coining the term "eurolegalism" to describe the hybrid, he shows how the political and organizational realities of the EU make this shift inevitable.